Crisis of knowledge and its malaise to the Muslim Ummah - Hashim, Che Noraini; Kayode, Bakare Kazeem (penseejournal.com, 2014)
The intellectual turmoil and knowledge vacuum facing mankind specifically the Muslim Ummah (Community) has come with a multitude of problems which requires new solutions. However, the angle of vision wherein these predicaments presented themselves before the Muslims is far different from anything they are accustomed to. Muslims of this present generation is going through "a crisis of knowledge and thought". This paper does not lay claim on providing an exhaustive solution or answers to the entire problem facing the Muslims Ummah, but rather, tries to present a chronicle of events and explanations to the following fundamental questions: why does crisis of knowledge exist among Muslims? In what ways has the crisis brings malaise to the Ummah? And how could the crisis be overcome?